Analysis of Gravity Data for Basement Depth Estimation of the Western Part of Java Island, Indonesia - Ananda, Riski; Azhari, Na'ila Yuni; Rahadinata, Tony; Grandis, Hendra (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
Studying the basement depth and fault structures is crucial for understanding basin geometry and fluid migration pathways. This study aims to understand basin geometry using gravity data in the Banten area, Indonesia, as a region with possible hydrocarbon prospects. Anomaly gradients derived from the Bouguer anomaly were conducted for fault analysis. Meanwhile, basement depth estimation was performed using Euler deconvolution, with a Structural Index (SI) of 0 and window sizes of 7 km × 7 km and 10 km × 10 km. Additionally, 3D inversion modelling with Grablox 1.6 was applied to model the sediment-basement interface. The anomaly gradient results correlate well with regional fault structures, and local structures align with high-gradient areas in southern Banten. Furthermore, high-gradient values are associated with hydrocarbon seep locations, indicating fractures or faults transporting hydrocarbons. The depth estimations of Euler deconvolution cannot accurately identify the discontinuities forming the basin. However, they align reasonably well with the sediment-basement interface of the density model. The model reveals basin structures up to 7.8 km deep in the Bogor Basin and its surroundings, consistent with low residual anomaly areas, aiding in the early estimation of lateral basin boundaries.